Effect of brand image on consumer purchasing behaviour on clothing: Comparison between China and the UK's consumers - Tam, Kwok Keung (2007)
Brand is a powerful tool to attract more consumers to buy particular products. Some may even regarded it as equity as it can add values to the products. This study examines the factors which contribute to brand equity in the clothing industry, comparing the consumer behaviour between the British and Chinese respondents based on the four respects of brand equity, namely brand awareness, perceived quality, brand loyalty and brand association.